2(7v-3)=20v-6(v+1)

Simple and best practice solution for 2(7v-3)=20v-6(v+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7v-3)=20v-6(v+1) equation:


2(7v-3)=20v-6(v+1)

We simplify the equation to the form, which is simple to understand
2(7v-3)=20v-6(v+1)

Reorder the terms in parentheses
+(+14v-6)=20v-6*(v+1)

Remove unnecessary parentheses
+14v-6=+20v-6+*(+v+1+)

Reorder the terms in parentheses
+14v-6=20v+(-6v-6)

Remove unnecessary parentheses
+14v-6=+20v-6v-6

We move all terms containing v to the left and all other terms to the right.
+14v-20v+6v=-6+6

We simplify left and right side of the equation.
v=0

0=0

This equation is an identity, so all real numbers are solutions.

See similar equations:

| 9x-13=31 | | 4x+9=6x+7 | | 25k^4-1=0 | | -4(-12-15b)=-5(-12b-12) | | 5x-20=3(x-4) | | -7p=42 | | -5/2(w-1)+3=18 | | X-4-3x=-2x-4 | | b-4=3b | | 12=-3v+6b | | -7(-2g+4)+19=-9+14g | | 3(n-4)=-42 | | 9(2X+5)=3X | | 1x+2=4x-12 | | 11-4c=3 | | 3(x-14)+(x+30)/5=x+2(3x-15)/5 | | (x+7)(2x-3)=140 | | 7x+1=8-4x | | -45+8v=-3(1+10v)-4v | | -10+14u=-8(-3u+15) | | x+2x+x-12=180 | | 25=4.5+12 | | -(-10t+2)+6=8-3t | | -3(-10-4s)=-2(-15-6s) | | 0=n-1-3 | | 21=15+4(m-2) | | Y(3x-4)=3(x-2) | | 10+x=4x+2x | | -6x+5=-94+5x | | 3(16m+13)=9+8(6m+9) | | 6=-2n-6(3n+2) | | 36y^3-9=y-324y^2 |

Equations solver categories